Development of conducive business environment for private sector investors following public procurement rules using World Bank fund in the ‘Support to Development of Kaliakoir Hi-Tech Park/IT Parks Project’ - Islam, Mohammad Atiqul (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2021.